2016
DOI: 10.1055/s-0041-108949
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Umfrage zur Identifizierung von Evidenzlücken in der HNO-Heilkunde

Abstract: The cited knowledge gaps then needed to be verified or refuted and clarified based on research of the literature as to whether the existing evidence actually reached healthcare providers in the form of guidelines, publications, conferences or continuing training for application in daily practice. Other steps would include prioritizing future research, evidence mapping, deciding on further systematic reviews, and targeted studies in conjunction with procuring third-party funding and in cooperation with patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
1
0
3
Order By: Relevance
“…Typically the return rates in professional fields for online survey is around 29%-45%. 5,6 A study reported that web surveys gave 44.1 % of return rate with time period of 5.27 days compared to 26.27% for mails. Mails also had longer time period for return of responses i.e.…”
Section: Response Ratementioning
confidence: 99%
“…Typically the return rates in professional fields for online survey is around 29%-45%. 5,6 A study reported that web surveys gave 44.1 % of return rate with time period of 5.27 days compared to 26.27% for mails. Mails also had longer time period for return of responses i.e.…”
Section: Response Ratementioning
confidence: 99%
“…Die Responserate von 32 % erscheint vor diesem Hintergrund zunächst zwar nicht all zu hoch und sollte nach Möglichkeit in einem solchen „setting“ mindestens 40 % betragen [ 33 ]. Bei Betrachtung anderer Onlineumfragen in der Hals-Nasen-Ohren-Heilkunde in Deutschland entspricht allerdings die vorliegende Antwortrate durchaus den dort erzielten Werten zwischen 30 und 40 % [ 12 , 27 ]. Bezogen auf die einzige vergleichbare Studie [ 10 ] war die Responserate sogar deutlich höher.…”
Section: Diskussionunclassified
“…Gebiet kam es aus dem ambulanten Bereich nur zu einer Rücklaufquote von unter 20 %[40].Tinnitus ist nicht auf eine einzelne Krankheit oder pathologische Veränderung zurückzuführen, sondern nur ein Symptom, das für einige, aber nicht für alle Betroffenen belastend ist[41].Emotionale Faktoren, wie Depressionen, Angst-und somatoforme Störungen stellen ernst zu nehmende Prädiktoren für eine schlechte Prognose der Tinnitusentwicklung dar, entsprechend hoch ist die Rate an Komorbiditäten [Übersicht z. B. in 2].…”
unclassified